2021
DOI: 10.21203/rs.3.rs-857423/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Metformin When Combined With Neoadjuvant Chemotherapy in Breast Cancer Patients

Abstract: BackgroundMetformin has been used to treat type 2 Diabetes Mellitus since long time. It has two proposed anti-neoplastic mechanisms, direct (insulin-independent) and indirect (insulin-dependent) actions. PurposeTo assess the effect of Metformin on pathological response when combined with neoadjuvant chemotherapy in breast cancer. Material and MethodsA prospective study included stage II, III non-diabetic breast cancer patients who received neoadjuvant chemotherapy in our center during the period from May 2017 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…23 El-Khayat et al found that the addition of metformin significantly increased the rate of pathologic complete response to neoadjuvant chemotherapy in breast cancer. 24 In contrast, Lopez-Bonet et al observed that the addition of metformin did not alter the pathologic complete response rate of human epidermal growth factor receptor 2-positive breast tumours treated with neoadjuvant trastuzumab, anthracycline and taxane. 25 A study in ovarian cancer patients revealed that metformin increased the proportion of cancer cells that co-expressed the stem cell-like markers aldehyde dehydrogenase (ALDH) and CD133.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…23 El-Khayat et al found that the addition of metformin significantly increased the rate of pathologic complete response to neoadjuvant chemotherapy in breast cancer. 24 In contrast, Lopez-Bonet et al observed that the addition of metformin did not alter the pathologic complete response rate of human epidermal growth factor receptor 2-positive breast tumours treated with neoadjuvant trastuzumab, anthracycline and taxane. 25 A study in ovarian cancer patients revealed that metformin increased the proportion of cancer cells that co-expressed the stem cell-like markers aldehyde dehydrogenase (ALDH) and CD133.…”
Section: Introductionmentioning
confidence: 93%
“…For example, Yee et al reported that the addition of metformin modestly increased the pathologic complete response rate to neoadjuvant ganitumab in breast cancer patients 23 . El‐Khayat et al found that the addition of metformin significantly increased the rate of pathologic complete response to neoadjuvant chemotherapy in breast cancer 24 . In contrast, Lopez‐Bonet et al observed that the addition of metformin did not alter the pathologic complete response rate of human epidermal growth factor receptor 2‐positive breast tumours treated with neoadjuvant trastuzumab, anthracycline and taxane 25 .…”
Section: Introductionmentioning
confidence: 99%